PENGUJIAN REAKSI TERHADAP SINYAL KINERJA PERUSAHAAN PUBLIK INDONESIA MELALUI PEMECAHAN SAHAM - Saiful, Saiful (JURNAL FAIRNESS, 2015)
Most previous studies found that the market reacted positively to the announcement of firms stock split. Those positive investor perception is based on their expectation of a better future firm performance in the future that informed through stock splits. This study provide an empirical evidence on investor reactions on stoc split announcement and the current earnings quality and future profit as well of 20 stock split indonesian public listed during the period2000 to2008. This study found that investor of Indonesian stock exchange is not react to firm stock split announcement. This study also found that stock split firm report lower future performance and lower current earning quality. This findings imply that indonesian investor reaction to stock split announcemenet depend on their percived of current and future stock split firm performance.